DESCRIPTION OF KNOWLEDGE AND SOIL TRANSMITTED HELMINTHS (STH) CONTAMINATION ON CABBAGE (Brassica oleracea L.) AND BASIL (Ocimum sanctum L.) IN LALAPAN MERCHANTS IN X VILLAGE, SOUTH DENPASAR - Putra, I Putu Bagus Krisna Pramana; Laksemi, Dewa Ayu Agus Sri; Diarthini, Ni Luh Putu Eka; Damayanti, Putu Ayu Asri (E-Jurnal Medika Udayana; Vol 13 No 8 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i08.P11, 2024)
Soil Transmitted Helminths (STH) infection is caused by nematodes transmitted through the soil. In general, such as Ascaris lumbricoides , Trichuris trichiura , hookworm, or Strongyloides stercoralis . A habit of consuming not hygienic vegetables or lalapan like cabbage ( Brassica oleracea L.) and basil ( Ocimum sanctum L.) is a risk for transmission. Lalapan merchants play important role in food preparation, as of knowledge and good food safety are required. The study aimed to describe STH knowledge, personal hygiene, water sources, lalapan merchant’s safekeeping, and STH contamination in cabbage and basil. The study is descriptive cross-sectional with STH knowledge, STH determinants questionnaire, and microscopic identification with NaCl 0,9% sedimentation method for instruments. The sample was all lalapan merchants in X Village, South Denpasar. Total there are 26 respondents. 84,62% of respondents are male, 34,6% at age 17-25 years old, and 65,4% senior high school as tertiary education. Obtained, lalapan merchant’s knowledge is not good at 57,7%. All respondents with clean fingernails and 92,3% practiced hand washing. Water sources from municipal waterworks (76,9%), clean merchant’s water containers (88,5%), and closed (92,3%). The food safekeeping was clean, separated in 92,3%, and closed for 88.5% of respondents. Contamination was found in 8,6% of 58 samples. Hookworm eggs in three basil (10,3%) and one cabbage (3,4%), one larva STH in basil (3,4%). Although knowledge is not good, personal hygiene is widely practiced. Water sources are mostly from municipal waterworks. The food safekeeping is separated, closed, and clean. It’s necessary to improve the knowledge about STH infection to realize food safety principles. Keywords : soil transmitted helminths, STH knowledge, STH contamination